Calcium silicate-based cements cause environmental stiffness and show diverse potential to induce osteogenesis in human osteoblastic cells - Santiago, Marcos Coelho; Gomes-Cornélio, Ana Lívia; de Oliveira, Laudimar Alves; Tanomaru-Filho, Mario [UNESP]; Salles, Loise Pedrosa (Springer Nature, 2021)
Calcium silicate-based cements differ markedly in their radiopacifiers and the presence of calcium sulfate, aluminates, carbonates and other components that can affect their biological properties. This study aimed to compare the biological properties of six calcium silicate cements in human osteoblastic cell culture (Saos-2 cells): Bio-C Repair (Bio-C), PBS HP (PBS-HP), Biodentine (Biodentine), MTA Repair HP (MTA-HP), NeoMTA Plus (NeoMTA-P), and ProRoot MTA (ProRoot). After exposure to these materials, the cells were analyzed by MTT, wound healing, cell migration, and alkaline phosphatase activity (ALP) assays, real-time PCR (qPCR) analysis of the osteogenesis markers (osteocalcin or bone gamma-carboxyglutamate protein, BGLAP; alkaline phosphatase, ALPL; bone sialoprotein or secreted phosphoprotein 1, BNSP), and alizarin red staining (ARS). Curiously, the migration rates were low 24–48 h after exposure to the materials, despite the cells showing ideal rates of viability. The advanced and intermediate cell differentiation markers BGLAP and BNSP were overexpressed in the Bio-C, MTA-HP, and ProRoot groups. Only the Biodentine group showed ALPL overexpression, a marker of initial differentiation. However, the enzymatic activity was high in all groups except Biodentine. The mineralization area was significantly large in the NeoMTA-P, ProRoot, PBS-HP, MTA-HP, and Bio-C groups. The results showed that cellular environmental stiffness, which impairs cell mobility and diverse patterns of osteogenesis marker expression, is a consequence of cement exposure. Environmental stiffness indicates chemical and physical stimuli in the microenvironment; for instance, the release of cement compounds contributes to calcium phosphate matrix formation with diverse stiffnesses, which could be essential or detrimental for the migration and differentiation of osteoblastic cells. Cells exposed to Bio-C, PBS-HP, ProRoot, NeoMTA-P, and MTA-HP seemed to enter the advanced or intermediate differentiation phases early, which is indicative of the diverse potential of cements to induce osteogenesis. Cements that quickly stimulate osteoblast differentiation may be ideal for reparative and regenerative purposes since they promptly lead to dentin or bone deposition.